Is Non-Timber Forest Product Harvest Sustainable in the Less Developed World? A Systematic Review of the Recent Economic and Ecological Literature - Stanley, Denise; Voeks, Robert; Short, Leaa (Ethnobiology and Conservation, 2012)
Non-timber forest products (NTFPs) provide material subsistence and cash income to millions of rural people, particularly in less developed countries. This paper offers a systematic review of recent trends (2000-2010) in the ecological and economic sustainability of NTFPs. Of 101 NTFP ecological studies, most addressed harvest consequences at the population-individual level (62.4%), and over half (52.5%) were carried out in Latin America. Nearly two-thirds of research (63.3%) reported that extraction was sustainable or likely to be so, compared to less than one-fifth (17.8%) that found it to be unsustainable. Extractive enterprise in Latin America was most often reported as ecologically sustainable (82.6%), and least often in Asia (58.8%). Because little of the economic NTFP literature identifies whether extractive returns meet the financial needs of extractors, at least on a daily basis, we outline economic sustainability criteria in terms of whether returns surpass an absolute poverty line or alternative wage. Of the 71 articles presenting financial data, over two-thirds met or exceeded the threshold of economic sustainability. Roughly 75% of studies demonstrated that gatherers earned more than USD$2 PPP/day (the international absolute poverty line) or more than a local wage. These positive results do not, however, demonstrate that gathering reduces long-term poverty because forest dependence, and likely tenure security, remains low among these populations. Caution must be exercised in terms of extending these results into the future, as changing economic conditions, rates and sources of habitat modification, and climate change all point to increased extractive pressures on tropical forests and savannas.